Penggunaan Computer Based-Test di Indonesia: Utopia atau Keniscayaan? - Arief Fahmie (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2003)
The use of computere technology in psychology has been increasing rapidly. Commonly, computer is used at research activities, exspecially for analizing data. Computer using should be increased in application of psychology in Indonesia. In other countries, many psychologists are using computer when they are testing, councelling, or building research (not only for analizing data). Computer-based test is one of applied technology in psychological testing. Actually, the application of computer-based test has big opportunity in Indonesia because people have good appreciation on computer technology development, and they use computer in some activities. Amount of CPU (Computer Personal Unit) has been increasing both in institutes of education and government, as well as in bussiness organizations. On the other hand, there are some problems in applying computer-based test which must be solved. Breaking the intellectual rights is the big difficulty to protect the new technology. Government must uphold the laws. The other problem is innovation of psychologists both on academic and application area at low degree. It must be developed with personal way as well as organizational way continously. If it can not be conducted, developmental of psychology in Indonesia will be left behind rather than the other countries.Keywords: Computer Based-Test, analizing data